Pembelajaran Sains di Luar Kelas: Membangun Minat dan Pengetahuan Sains dalam Kehidupan Sehari-hari: (Studi Kasus di SMPN 1 Tanggulangin) - Satunggale Kurniawan, (SEARCH: Science Education Research Journal, 2025)
Science learning outside the classroom has become one of the effective methods in increasing students' interest and understanding of scientific concepts. This study aims to explore the implementation of science learning outside the classroom at SMP Negeri 1 Tanggulangin and its impact on students' interest and understanding. This study uses a qualitative approach with a case study design, involving observation, interviews with teachers and students, and analysis of learning documents. The results of the study indicate that science learning outside the classroom can increase students' interest in science because the learning experience is more interactive and contextual. In addition, students also showed an increase in understanding of science concepts because they were able to relate theories to phenomena directly observed in the surrounding environment. However, this study also identified several challenges in implementing this learning, such as limited facilities and limited time in the curriculum. This study highlights the importance of support from schools and education policies to ensure the sustainability and effectiveness of science learning outside the classroom. Thus, experiential learning outside the classroom can be a significant strategy in improving the quality of science education in Indonesia.